PERSEPSI GENERASI Z TERHADAP GLORIFIKASI PERNIKAHAN DINI OLEH GUS ZIZAN PADA MEDIA SOSIAL TIKTOK - Ana Nurfita; Karnia Febrianti; Margeritha Laga; Nganti Triwati; Winin Saffanah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Child marriage remains a pressing issue in Indonesia despite the existence of regulations that set a minimum legal age for marriage. The marriage of Gus Zizan to a 16-year-old santriwati in 2024 illustrates how this practice gains both social and religious legitimacy, while simultaneously being glorified through social media. This study aims to analyze how Generation Z constructs social perceptions of child marriage and to examine the role of Gus Zizan in its glorification on TikTok. The research employs a qualitative approach using netnography and in-depth interviews with several Generation Z informants. The findings reveal that visual representations and religious-romantic narratives on TikTok shape Generation Z's perception that early marriage is an ideal choice, reinforced by social validation and parasocial relationships with public figures. Limited digital literacy renders adolescents vulnerable to uncritical acceptance of viral narratives, allowing their life standards and expectations to be shaped more by social media algorithms than by social realities. Furthermore, Gus Zizan's creative religious content significantly strengthens the glorification of child marriage, although it potentially generates adverse impacts such as limited educational aspirations, gender inequality, and socio-economic vulnerability. This study highlights the importance of digital literacy and ethical online preaching to prevent the normalization of child marriage among youth. Keywords: Generation Z, TikTok, child marriage, social perception, religious influencer